Understanding The Cultural Values in Traditional Sundanese Parenting: A Narrative Literature Review - Indah, Fufut Tri Nur; Hastuti, Dwi; Yuliati, Lilik Noor (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study aims to consolidate and synthesize the existing literature on traditional parenting within the Sundanese Tribe using a narrative methodology. Employing a narrative literature review, this research integrates findings from various sources to comprehensively understand the cultural values inherent in traditional Sundanese parenting. The research questions were formulated using the PICO framework, focusing on the population of cultural values, the intervention of examining these within existing parenting literature, and the outcome of understanding unique cultural values. Data were sourced from Google Scholar and ScienceDirect, covering publications between 2019 and 2024. The findings highlight the centrality of spirituality and religiosity in Sundanese parenting, which intertwines religious teachings with everyday practices. Traditions such as rituals during pregnancy, childhood, and marriage play a crucial role in shaping social behaviors and instilling moral values. Mystical practices like pamali are also significant, serving as cultural norms that guide conduct and promote community harmony. The implications of these findings are significant for both academic research and practical applications, offering insights into educational programs, policies, and future research directions. However, limitations include potential biases from the reliance on existing literature and the focus on a single ethnic group, suggesting a need for further empirical and comparative studies.